Infidelity Goes Online: Communicating About Sexual Health in Personal Ads When Seeking Extra-Dyadic Relationships on Craigslist. Issue 2 (3rd April 2018) - Denes, Amanda; Speer, Annika C.
Abstract: Objectives : The present study explored married and partnered individuals' ads on Craigslist seeking extra-dyadic sexual relationships. An analysis of the ads containing words related to health and safety was conducted to better understand the ways that individuals communicate about safe sex when seeking extra-dyadic relationships online. Methods : A total of 819 ads containing 6, 279 words were analyzed. Thematic analysis revealed that the words used in the ads fell into 8 unique categories, with one category comprising words related to health and safety. Results : The results revealed that men seeking men used more words related to health and safety than men seeking women, women seeking men, and women seeking women, though ads within all 4 groups noted health and safety concerns. For men seeking women, broader issues of safety (often pertaining to meeting up) were also expressed, and for women seeking men, issues of discretion arose. Lastly, women seeking women were the only group to mention polyamorous or nonmonogamous relationships, in addition to expressing concerns about sexual safety. Conclusions : The findings revealed that partnered or married men seeking sexual activity with other men posted the most ads and had the largest percentages for several key words related to safe sex, though such concerns were also prevalent in the ads of men seeking women, women seeking women, and to a limited degree (given the small sub-sample), women seeking men. These results suggest that interventions should aim at encouraging individuals who seek relationships online to not only state safe sex preferences and concerns, but also to continue such conversations and implement safe sex behaviors in offline contexts.